The Biology of the First 1,000 Days (Taylor & Francis, 2023)
The first 1,000 days, from conception to two years of age, is a critical period of growth and development. Exposures to dietary, environmental, hormonal, and other stressors during this window have been associated with an increased risk of poor health outcomes, some of which are irreversible. The book addresses this crucial interval of early life across biological disciplines, linking concepts related to all biological fields to outcomes during the first 1,000 days (e.g. fetal growth and pregnancy outcomes) and beyond (e.g. gut microbiome and cardiovascular disease later in life). The strength of this book lies in its cross-disciplinary nature.